TINJAUAN YURIDIS HAK KREDITOR PEMEGANG HAK TANGGUNGAN PERTAMA DALAM PELELANGAN BUDEL KEPAILITAN - Fenni Ciptani Saragih (PREMISE LAW JURNAL, 2013)
Bankruptcy was a form of general confiscation covering all assets of the debtor for the benefit of creditors. Article 55 chapter (1) of Act 37, 2004 stated that the lender Mortgage holders which were not affected by the bankruptcy so that the execution would be able to exercise the rights even though the debtor was declared bankrupt. Article 56 chapter (1) of Act 37 of 2004, the execution creditor the right Mortgage holders might be suspended for a maximum period of 90 days from the date of the decision of bankruptcy so they could still carry out the execution right, even though the debtor was declared bankrupt. Legal issues that arouse in a bankruptcy auction for the Mortgage boodle the explanation of Article 59 chapter (2) wider than the norm, as the holder of Mortgage bank registered with the security bill on behalf of shareholders or a third party, auction buyers obtained a problem because there were security certificates Mortgage-holders so it isn’t canceled by HT holders.